Solar Drying as an Eco-Friendly Technology for Sewage Sludge Stabilization: Assessment of Micropollutant Behavior, Pathogen Removal, and Agronomic Value - An-nori, Amal; Ezzariai, Amine; El Mejahed, Khalil; El Fels, Loubna; El Gharous, Mohamed; Hafidi, Mohamed (Frontiers in Environmental Science, 2022)
Sewage sludge (SS) is a biosolid that includes nutrients, organic matter, and a mixture of micropollutants and pathogens. Regarding its final disposal, several criteria should be met to avoid the dissemination of the included micropollutants in the environment. Hence, an adequate treatment prior to SS disposal is highly required. Solar drying is being acknowledged as a sustainable process of SS treatment, yet it is still unclear to what extent this technique is efficient. This review aimed to assess the impact of solar drying on the composition of SS from environmental and agronomic standpoints. Herein, we present the state-of-the-art with regard to solar drying efficiency in terms of water content reduction, DM increase, agronomic parameters evolvement, and micropollutant stabilization including pathogens, heavy metals (HMs), and organic micropollutants. The reviewed literature is mostly focused on two drying cycles: summer and winter, thus addressing the extreme conditions met within a year with respect to temperature. Under different climatic conditions, more than 80% of dry matter is reached during summer. In winter, the efficiency decreases to an average of 50% of DM. Negatively correlated to DM content, pathogen concentration in SS significantly decreased, while DM increased. Thus, more efficiency in terms of pathogen abatement is reported in summer than in winter (e.g., 96% against 60% during summer and winter, respectively, under semi-arid climate). The high reliance of solar drying efficiency on weather has been deduced in terms of DM content increase and pathogen removal. Where climatic conditions are not favorable for solar drying, hybrid design and liming are the highly recommended methods to remove pathogens from SS. A few studies on the fate of HMs in SS during solar drying concluded that solar drying does not involve any removal mechanisms. Changes in HM speciation in solar-dried sludge were reported highlighting a decrease in their mobility. As for organic micropollutants (PAHs and antibiotics), only their occurrence in SS is reported in the literature, and their behavior during the solar drying process is still not addressed. This review allowed concluding the following: 1) solar drying is a sustainable, relevant process for SS handing in terms of volume reduction and pathogen removal, particularly in semi-arid regions; 2) solar drying does not lower the SS agronomic value and does not remove HMs, but under semi-arid climate, it changes HM speciation and reduces their mobility. The gap in research regarding organic micropollutant and heavy metal behavior during SS solar drying has been emphasized as a way forward for research within this topic. Hence, more research is required to help stakeholders decide on the feasibility of an agricultural disposal of solar-dried sludge.